Dinamika Kelembagaan Sektor Pariwisata di Kabupaten Ponorogo - Yusuf Adam Hilman; Titing Kartika (Indonesian Journal of Tourism and Leisure, 2020)
Ponorogo regency has a variety of tourism resources, potentially developed to increase the tourism sector. This study aims to analyze the strategy of Ponorogo regency in governing the tourism sector based on strength, weakness, opportunity, and threat (SWOT). Using descriptive qualitative approach, this research was conducted in Ponorogo regency. The results indicate that Ponorogo has various tourism sources, such as nature, culture, art, religion, and gastronomy, as the strength. The weakness is that there are many tourism events not well managed by the government. The opportunity is extensive funding support from the government. The threat is the conflict in managing government grants. In addition, the government of Ponorogo regency is successful in delivering 66 tourism ceremonies using local regulation in order to change the threat to be the strength.